Scientific Outcome as a Result of Logical-Methodological Analysis - Berkov, Vladimir (WISDOM, 2014)
The paper recaps the analysis of the concept of scientific outcome from logical-methodological standpoint with particular reference to the pertinent nomenclature of its definition and typology. The research establishes the major characteristics attributed to the scientific outcome materialized and gained in the course of research work (within the framework of subject –object relationship), namely: the authenticity and relevance in terms of the academic metalanguage and within the dialogue process (subject – subject relationship). The article reveals the conditions and pre-settings necessary for any scientific outcome to emerge as a discovery. The author sets forth the idea of submitting scientific dissertations (research papers) to evaluative description via interrogative logic.